The Model of Environmental Furure City of Japan: Environmental Policy of Kitakyushu City - Ахaпов Е. А. (Journal of Oriental Studies, 2018)
The article examines the environmental problems of the city of Kitakyushu since the second half of the twentieth century to the present, and reviews the main reforms of the four city administrations regarding environmental policies to prevent industrial pollution and improve the state of the city’s environment. Particular attention was paid to the process of transformation from an industrially polluted city to the transition to the environmental future city of Japan. An example of the Kitakyushu environmental future city model is considered to be a source of valuable data for the Republic of Kazakhstan, which implements the state program of forced industrialinnovative development and the concept of a green economy for entry into the industrial-economic developed states (OECD). It is assumed that this article, from a practical point of view, plays an important role in improving the quality of state programs in the framework of the state environmental policy pursued by the Government of the Republic of Kazakhstan.